Development of the minimum competency assessment numerical instrument (AKM) in the economic context for junior high school students - Santy, Intan Safira Dwi; Mutaqin, Anwar (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
Development of 21st century education requires students to have literacy skills. National Assessment, which is the Minimum Competency Assessment (AKM) as a basic competency needed by students so that a numeracy assessment is needed as a source of training to improve students' numeracy skills. Study uses the Research and Development method with the ADDIE model. Subjects were 10 students at empirical validity (small-scale trials) and 46 students at implementation (large-scale trials). This study consisted of a needs analysis questionnaire, a student response questionnaire, and a numeration test instrument totaling 15 questions (13 multiple choices, 2 short entries). The results obtained by 6 material expert validators of 0.93 are categorized as very valid, consistent reliability on small-scale trials is 0.79 and the reliability of large-scale trials of 0.70 is categorized as high, the distinguishing power of 10 items is categorized as high and 5 items are categorized as high. items categorized as low, and the level of difficulty obtained 2 items with difficult and easy categories, and 11 items categorized as medium. The results of the student questionnaire obtained 70.25 categorized as good. To produce valid instrument items and can be used as a source of practice to improve students' numeracy skills.